Buried in water, burdened by nature: resilience carried the iron age people through Fimbulvinter - Oinonen, Markku; Alenius, Teija; Arppe, Laura; Bocherens, Hervé; Etu-Sihvola, Heli; Helama, Samuli; Huhtamaa, Heli; Lahtinen, Maria; Mannermaa, Kristiina; Onkamo, Päivi; Palo, Jukka; Sajantila, Antti; et al. (PLOS ONE, 2020)
Levänluhta is a unique archaeological site with the remains of nearly a hundred Iron Age individuals found from a water burial in Ostrobothnia, Finland. The strongest climatic downturn of the Common Era, resembling the great Fimbulvinter in Norse mythology, hit these people during the 6th century AD. This study establishes chronological, dietary, and livelihood synthesis on this population based on stable carbon and nitrogen isotopic and radiocarbon analyses on human remains, supported by multidisciplinary evidence. Extraordinarily broad stable isotopic distribution is observed, indicating three subgroups with distinct dietary habits spanning four centuries. This emphasizes the versatile livelihoods practiced at this boundary of marine, freshwater, and terrestrial ecosystems. While the impact of the prolonged cold darkness of the 6th century was devastating for European communities relying on cultivation, the broad range of livelihoods provided resilience for the Levänluhta people to overcome the abrupt climatic decline.
Gesehen am 30.03.2021